The effects of dexamethasone, bupivacaine and topical lidocaine spray on pain after tonsillectomy - Kaygusuz, I; Susaman, N (Elsevier Sci Ireland Ltd, 2003)
Objective: To compare the administration of bupivacaine hydrochloride, dexamethasone and lidocaine hydrochloride in decreasing post-tonsillectomy pain. Methods: Eighty patients were enrolled in the study in ENT Clinic, Firat University, and in ENT Clinic Elazig SSK Hospital, Elazi (Turkey). Children between 6 and 14 years of age referred to our department for bilateral tonsillectomy for either recurrent tonsillitis or tonsillar hypertrophy. Data from 80 patients were analyzed. The first group had bupivacaine hydrochloride. The second group had dexamethasone infiltrated around each tonsil. The third group was given equal doses of 10% lidocain hydrochloride sprayed on the tonsillectomy fossa four times a day, and a placebo group received 9% NaCl applied to the tonsillar fossa four times a day. Pain scores, determined by visual analog scale, were obtained in the first, third and seventh postoperative days. Results: Pain scores in the postoperative period were identical in the first, third and seventh postoperative days. According to VAS results the groups were compared on the basis of postoperative pain. In the first postoperative day, the difference between bupivacaine-placebo, dexamethasone-placebo and lidocaine-placebo groups was found to be statistically significant (P < 0.05). Nevertheless the difference between bupivacaine-dexamethasone, bupivacaine-lidocaine and dexamethasone-lidocaine were not significant (P > 0.05). In the third postoperative day, the difference between bupivacaine and lidocaine group found to be statistically significant (P < 0.05). In the seventh post-operative day the results of bupivacaine, dexamethasone, lidocaine and placebo groups were similar (P > 0.05). Conclusion: Bupivacaine, Dexamethasone and Lidocaine nasal aerosol decreased the pain significantly in the first postoperative day when it was compared with the placebo group. These three medicines can be used to reduce pain for children during the postoperative period applied tonsillectomy during the post-operative period. But lidocaine was more preferable, reducing pain in the third postop day better than bupivacaine. (C) 2003 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: children; tonsillectomy; pain; bupivacaine; dexamethasone; lidocaine